Morpho-histochemical characterization of salivary gland cells of males of the tick Rhipicephalus sanguineus (Acari: Ixodidae) at different feeding stages: description of new cell types - Furquim, Karim Christina Scopinho [UNESP]; Bechara, Gervasio Henrique [UNESP]; Mathias, Maria Izabel Camargo [UNESP] (Springer, 2010)
This study describes the changes undergone by cells of the salivary glands of unfed and feeding (at day two and four post-attachment) Rhipicephalus sanguineus males, as well as new cell types. In unfed males, types I and II acini are observed with cells undifferentiated, undefined 1 and 2 (the latter, with atypical granules), a, c1 and c3; type III is composed of cells d and e; and type IV present cells g. In males at day two post-attachment, type I acini exhibit the same morphology of unfed individuals. An increase in size is observed in types II, III, and IV, as cells are filled with secretion granules. Some granules are still undergoing maturation. In type II acinus, cells a, b and c1-c8 are observed. Cells c7 and c8 are described for the first time. Cells c7 are termed as such due to the addition of polysaccharides in the composition of the secretion granules (in unfed individuals, they are termed undefined 1). Type III acini exhibit cells d and e completely filled with granules, and in type IV, cells g contain granules in several stages of maturation. In males at day four post-attachment, type I acini do not exhibit changes. Granular acini exhibit cells with fewer secretion granules, which are already mature. In type II acini, cells a, b, c1-c5 are present, type III exhibit cells d and e, and type IV contain cells g with little or no secretion. This study shows that in the salivary glands of R. sanguineus males, cells a, c1, and c3 of type II acinus, and cells d and e of type III do not exhibit changes in granular content, remaining continuously active during the entire feeding period. This indicates that during the intervals among feeding stages, gland cells reacquire the same characteristics found in unfed individuals, suggesting that they undergo reprogramming to be active in the next cycle.
Keywords: Rhipicephalus sanguineus; Male tick; Salivary gland; Cell cycle; Cell reprogramming; Feeding stages